Market outlook for the Singapore bunkering market from 2011-2015 - Liew, Wei Lin. (2012)
This research encompasses and analyses a number of market fundamentals to determine the outlook and profitability of investing in Singapore‟s bunkering market from 2011 to 2015. It includes three volumes; with Volume I focusing on the demand factors, Volume II on the supply tonnage, and Volume III analyzing the freight rates movement determined by Volume I and II, as well as evaluating the profitable potentials and strategies in this segment. In Volume II of this research, drivers that impact the supply of bunker tankers as well as freight rates are analysed. A fleet projection is done based on regulatory requirements that affects the scrapping age and the requirements for fleet renewal. As a result, it is forecasted that there will be an oversupply in supply tonnage due to the renewal of „Large‟ bunker tankers. Financing of these renewals will hence be relied on local banks instead of international banks given the current financial situation where restrictions are still tight. This will result in a negative impact on the oversupply issue as operators are not tied down to restrictive financial sources. The availability of floating storages in Port of Tanjung Pelepas also has an impact on supply. However, due to limited information, this factor is considered under limitations.